Finger-specific effects of age on tapping speed and motor fatigability - Heimhofer, Caroline; Neumann, Amira; Odermatt, Ingrid; Bächinger, Marc; Wenderoth, Nicole (Frontiers in Human Neuroscience, 2024)
Increased motor fatigability is a symptom of many neuromuscular and neurodegenerative disorders. However, it is difficult to pinpoint pathological motor fatigability, since the phenomena has not yet been fully characterised in the healthy population. In this study, we investigate how motor fatigability differs across age. Given that many disorders involve supraspinal components, we characterise motor fatigability with a paradigm that has previously been associated with supraspinal mechanisms. Finger tapping at maximal speed results in a rapid decrease in movement speed, which is a measure of motor fatigability. We collected finger tapping data in a field experiment from the general population with a smartphone app, and we investigated age differences in maximal tapping speed, as well as the decrease in tapping speed for the index, middle, and little fingers. We found that the maximal tapping speed differed significantly between young (18 – 30 years, n=194) and aged (50 – 70 years, n=176), whereas the fatigability-induced relative decrease in movement speed did not differ between the age groups (average decrease: 17.0% ± 6.9% (young) vs. 16.5% ± 7.5% (aged) decrease). Furthermore, tapping speed and motor fatigability depended on which finger was used. These findings might relate to dexterity, with more dexterous movements being more resistant to fatigue. In this study, we provide a characterisation of motor fatigability in the general population which can be used as a comparison for clinical populations in the future.